Transitioning to Full Online Teaching During Covid-19 Crisis: The Associate Degree Nurse Faculty Experience - Kechi Iheduru-Anderson; Jo Anne Foley (SAGE Publishing, 2021)
As the COVID-19 crisis escalated in early 2020, schools of nursing and nursing programs in the United States and around the world shut down. Nurse faculty were forced transition to online teaching in a short time. Descriptive phenomenology was used to explore the experiences of associate degree nurse faculty who transitioned to online teaching during the early months of the COVID-19 pandemic. Inductive thematic analysis was performed on the interview data from 41 faculty teaching at associate degree nursing programs in the U.S. The findings of the study are presented under 6 main themes: stressful/overwhelming, feeling emotionally and physically exhausted, support, new knowledge and growth under pressure, new opportunities for nursing education, and leadership in times of crisis. To prevent the worsening of the nurse faculty shortage and help educate nurses for the future, nurse educators must be supported and recognized for their work during this period and beyond.